The Tunan Waterfall Ecotourism Development Strategy in Talawaan Village, Talawaan District, North Minahasa Utara. - Tarigan, Hemi Elda Br; Katiandagho, Theodora Maulina; Benu, Noortje Marsellanie (Jurnal Agroekoteknologi Terapan, 2024)
This study aims to identify the Tunan Waterfall Ecotourism Development Strategy in Talawaan Village, Talawaan District, North Minahasa Regency. This research was conducted during July 2023. The selection of respondents was done deliberately and determined. The data used are primary data and secondary data. Primary data was obtained by conducting direct interviews with respondents, completing questionnaires, and FGD (Focus Group Discussion), and secondary data was obtained from previous research related to this research. The total respondents were 25 people. Secondary data was also obtained through books obtained from local bookstores and the internet via Google Scholar in the form of books, journal articles, and theses related to the topic of this research, namely Waterfall Ecotourism Development Strategy. The results of the study show that the analysis on the SWOT matrix is obtained at the coordinates of 0.67: 1.08, which means that the position is in quadrant I (aggressive), namely supporting growth strategies (Growth), by maintaining the beauty of nature, not only the waterfall but the beauty along the way, as well as taking advantage of the strengths of tourist objects, such as the beauty of nature, the existence of river water that can be used as a place to swim, good accessibility, proximity, and others. Keywords: development strategy, ecotourism, waterfall, tourism factors Abstrak Penelitian ini bertujuan untuk mengidentifikasi Strategi Pengembangan Ekowisata Air Terjun Tunan di Desa Talawaan Kecamatan Talawaan Kabupaten Minahasa Utara. Penelitian ini dilaksanakan selama bulan Juli 2023. Pemilihan responden dilakukan secara sengaja dan ditentukan. Data yang digunakan adalah data primer dan data sekunder. Data primer diperoleh dengan melakukan wawancara langsung dengan responden, pengisian kuesioner dan FGD (Focus Group Discussion) dan data sekunder diperoleh dari penelitian yang sudah ada sebelumnya yang berkaitan dengan penelitian ini. Total responden sebanyak 25 orang. Data sekunder juga diperoleh melalui buku yang diperoleh dari toko buku lokal serta internet melalui google scholar berupa buku, artikel jurnal dan skripsi yang berkaitan dengan topik penelitian ini yaitu Strategi Pengembangan Ekowisata Air Terjun. Hasil penelitian menunjukkan analisis pada matriks SWOT diperoleh pada titik koordinat 0,67 : 1,08 yang artinya posisi tersebut berada pada kuadran I (agresif) yaitu mendukung strategi pertumbuhan (Growth), dengan mempertahankan keasrian alam bukan hanya air terjunnya tetapi keasrian sepanjang perjalanan, serta memanfaatkan kekuatan dari objek wisata, seperti keasrian alam, adanya aliran air sungai yang bisa dibuat sebagai tempat berenang, aksesibilitas yang baik, jarak yang dekat, dan lainnya.   Kata kunci: strategi pengembangan, ekowisata, air terjun, faktor faktor pariwisata.